Analysis and modeling of enhanced green fluorescent protein diffusivity in whey protein gels. (June 2019) - Luo, Qi; Sewalt, Erik; Borst, Jan Willem; Westphal, Adrie H.; Boom, Remko M.; Janssen, Anja E.M.
Abstract: During gastric digestion, hydrolysis of proteins by pepsin contributes largely to the breakdown of protein-rich food. We hypothesized that the effect of pepsin is limited by its diffusivity, which is co-determined by the food structure and the local pH in the food during digestion. To investigate the principle mechanism of enzyme diffusion in food matrices, we used enhanced green fluorescent protein (EGFP) as probe to study the diffusivity of proteins in whey protein isolate gels, using fluorescence correlation spectroscopy (FCS). Gels made with different ionic strength showed distinctive elastic moduli but did not show differences in diffusivity of EGFP. Some models for diffusion in hydrogels yield good description of the obtained data, and can approximate the enzyme diffusion in diverse food matrices. However, the enzyme pepsin is more complicated than the probe EGFP, to yield more accurate predictions, electrostatic and enzyme-substrate interaction also need to be considered. Graphical abstract: Unlabelled Image Highlights: We studied the diffusivity of green fluorescent protein in varied whey protein isolate gels. Protein volume fraction is the major determinant of diffusion hindrance in gels. Physics-based models were used to analyze the diffusion hindrance in gels. Some models can predict pepsin diffusion in foods and help understanding digestion.